A comparative study between calcium intake and low bone density among women (19-35 year) in urban area of Hyderabad, India - Syeda, Uzma Nabeela; Syeda, Nasreen (International Journal Of Community Medicine And Public Health, 2020)
Background: This paper is aimed at assessment of bone health in women aged between 19-35 years in the urban area leading a sedentary lifestyle. The objective of the study was to assess the bone density among the adult women and identify their risk of developing osteoporosis and to associate risk factors that may predispose them to osteoporosis. Methods: The methodology involved assessment of their anthropometric measurements and calculating Body mass index to identify obese and non-obese participants. A semi-quantitative food frequency questionnaire was framed to know the calcium intake of the diet along with the other nutrients and foods that favour and hinder the absorption of calcium was also studied along with their frequency of consumption. BMD test on all 51 participants is done and the T- score obtained compared with the WHO classification. Results: It was observed that 35% of the participants were having osteopenia, a condition where bones become weak than normal and may predispose to osteoporosis. The calcium content of the diet found to be lower than the RDA which is significant at p<0.05. Correlation analysis showed a weak negative correlation between the two variables i.e., calcium intake and bone mineral density rs=-0.03, p>0.05. Other factors that can contribute to the low bone mineral density was lack of exercise, obesity, genetic inheritance, H/o PCOS, hypothyroidism, consumption of coffee and carbonated beverages. Conclusions: Thus, it is concluded that these women are at risk of developing osteoporosis so dietary modification and change in lifestyle is necessary.